IMPLEMENTASI PELATIHAN APLIKASI CANVA PADA PENGABDIAN KEPADA MASYARAKAT DI KELAS X SMAN 4 BINJAI UNTUK MENINGKATKAN INOVASI SISWA PADA DESAIN GRAFIS - Dapot Tua Manullang; Episman Gea; Leonardo Fransiskus Sihotang; Tiamar Panggabean (CV SWA Anugerah, 2025)
This service discusses Canva training in class X of SMAN 4 Binjai to improve graphic design innovation in students. The Canva application is a simple graphic design application/platform that can be used by everyone. In the digital era, the use of technology is an important strategy to improve students' skills and innovation. The results of the implementation of PKM activities at SMAN 4 Binjai provide real changes to students where students can create their own designs from the Canva application so that they become provisions for the implementation of the learning they follow. From the competition activities and the results of the Canva training evaluation in class X of SMAN 4 Binjai where class X-7 won 1st place, class X-2 won 2nd place and class X-3 won 3rd place. This is the output produced from the implementation of activities, both introduction to theory, direct practice and evaluation of activities in the Canva application training in class X of SMAN 4 Binjai.